2012
DOI: 10.1128/jb.00976-12
|View full text |Cite
|
Sign up to set email alerts
|

Whole Surface Image of Mycoplasma mobile, Suggested by Protein Identification and Immunofluorescence Microscopy

Abstract: Mycoplasma mobile, a freshwater fish pathogen featured with robust gliding motility, binds to the surface of the gill, where it then colonizes. Here, to obtain a whole image of its cell surface, we identified the proteins exposed on the surface using the following methods. (i) The cell surface was labeled with sulfosuccinimidyl-6-(biotinamido) hexanoate and recovered by an avidin column. (ii) The cells were subjected to phase partitioning using Triton X-114, and the hydrophobic proteins were recovered. (iii) T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Gli349, MvspI, and DNA were localized at the neck, the head and body, and the body, respectively, in good agreement with previous studies (Fig. 1A) (12,13,55,58). P42 was colocalized with Gli349 but not with MvspI or with DNA localized in regions other than the neck, suggesting that P42 is involved in the gliding mechanism.…”
Section: Transformation Of M Mobilesupporting
confidence: 80%
See 3 more Smart Citations
“…Gli349, MvspI, and DNA were localized at the neck, the head and body, and the body, respectively, in good agreement with previous studies (Fig. 1A) (12,13,55,58). P42 was colocalized with Gli349 but not with MvspI or with DNA localized in regions other than the neck, suggesting that P42 is involved in the gliding mechanism.…”
Section: Transformation Of M Mobilesupporting
confidence: 80%
“…To date, the subcellular localizations have been clarified for 13 proteins in M. mobile (Fig. 1), and all proteins localizing at the neck part have been suggested to be involved in the gliding mechanism (3,22,55). In the present study, two other proteins were shown to be localized on the gliding machinery (Fig.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…The gliding machinery of M. mobile generates a force up to 27 pN, which enables cells to glide smoothly on a broad range of surfaces at a speed of 2.0-4.5 lm s 21 (Miyata et al, 2002). The M. mobile cell surface is covered by membrane-anchored proteins (Wu and Miyata, 2012). Examination of cells by electron microscopy revealed spike-like structures approximately 50 nm in length around the neck area of the bowling-pin-shaped cells (Miyata and Petersen, 2004).…”
Section: Mycoplasma Mobile Gliding Utilizes Tiny Legs Marching Unitarilymentioning
confidence: 99%